Quantile causality and dependence between crude oil and precious metal prices. (21st July 2020) - Shafiullah, Muhammad; Chaudhry, Sajid M.; Shahbaz, Muhammad; Reboredo, Juan C.
Abstract: This paper examines long‐run dependence and causality between oil and precious metal (gold, silver, platinum, palladium, steel, and titanium) prices across quantiles by exploiting their time series properties with the help of novel econometric techniques. The empirical results for the period 1990–2019 indicate that oil and metal prices are nonstationary across different quantiles and that cointegration patterns differ widely across quantiles. Causality running from oil to metal prices is quantile‐dependent and differs according to the metal, whereas upward and downward movements in metal prices have no causal effect on oil prices. These results have implications for investors and policymakers in terms of portfolio and risk management decisions.